Starch granular protein of high-amylose wheat gives innate resistance to amylolysis. (15th November 2020) - Li, Hai-Teng; Sartika, Rakhmi S.; Kerr, Edward D.; Schulz, Benjamin L.; Gidley, Michael J.; Dhital, Sushil
Highlights: High-amylose wheat starch (HAWS) has more granular protein content than wild type. Mass spectrometry Proteomics revealed the protein profile of HAWS. Granular-bound starch synthase (GBSS) content increases with amylose content. Relative abundance of major granular proteins in HAWS does not differ from wild type. Greater granular protein content in HAWS contributes to slower amylolysis. Abstract: Granular protein is an important structural feature in determining starch digestibility. High-amylose wheat starch (HAWS) with >80% amylose content contains more granular protein than wild-type starch. As analyzed by mass spectrometry-based proteomics, granular-bound starch synthase (GBSS) is the major granular protein in isolated starch materials. GBSS content increases with amylose content (Spearman's correlation, p < 0.05), whereas the abundance relative to other proteins is similar among starches. Multiple amylase inhibitors were also identified. From Michaelis–Menten analysis, HAWS has a similar K m (Michaelis constant) as wild type, suggesting initial enzymatic binding is similar. After the pre-digestion of proteins, wild type had a greater change in starch digestibility than HAWS, probably due to the latter having 'thicker' granular-protein layers and higher enzymatic resistance of substrate per se . Overall, the study suggests that the greater granular protein content in HAWS is a factor that contributes to slower amylolysis compared to wild type.